Dose-dependent stress response of esfenvalerate insecticide on common carp (Cyprinus carpio): Evaluating blood parameters and gene expression - Zemheri Navruz, Fahriye; Acar, Umit; Yılmaz, Sevdan; Kesbic, Osman Sabri (Elsevier BV, 2023)
Esfenvalerate is a pyrethroid insecticide used primarily in the agriculture sector for insect management. Esfenvalerate is effective against a wide range of harmful insects, including flies, cockroaches, locusts, and many other types of bugs. It is also known that esfenvalerate has toxic effects on aquatic organisms and poses significant environmental concerns. In this study, the aim is to subchronically examine the effects of sublethal concentrations of esfenvalerate insecticide on common carp (Cyprinus carpio) by assessing changes in blood parameters and resulting gene expression. For this purpose, common carp (Cyprinus carpio) were divided into 5 groups and exposed to 0.025, 0.05, 0.1, and 0.15 μg/L concentrations of esfenvalerate for a period of 14 days. Blood and liver tissue samples were collected from the fish that underwent weight and length measurements. The effects on gene expression levels of immune, antioxidant, and stress-related genes in the liver tissue, including SOD, GST, Cortisol receptor, HSP70, H+-ATPase, Na+/K+-ATPase, Catalase, and GpX, were evaluated, as were the hematological and serum biochemical parameters. Significant decreases were observed in the levels of hematocrit, hemoglobin, erythrocytes, triglycerides and total protein and catalase, H+-ATPase, and GpX gene expression. Glucose, cholesterol, alanine aminotransferase, aspartate aminotransferase, lactate dehydrogenase (LDH) and alkaline phosphatase (ALP), SOD, Cortisol receptor, Na+/K+-ATPase gene expression levels increased. As a result, it has been revealed that esfenvalerate insecticide causes oxidative stress in carp at all dose ranges.
Keywords: Adenosine Triphosphatases; Insecticides; Carps; Hydrocortisone; Superoxide Dismutase; Esfenvalerate; Gene Expression; Cyprinus Carpio; Catalase; Antioxidants; Oxidative Stress; Pyrethrins; Animals; Water Pollutants, Chemical